2019
DOI: 10.3389/fneur.2019.00661
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Gut Microbiota Dysbiosis and Chronic Systemic Inflammation After Cerebral Infarction in Cynomolgus Monkeys

Abstract: Background: The bidirectional interaction between the gut and brain after stroke through the immune-mediated pathway has been studied. However, the long-term effects of gut microbiota and systemic immune homeostasis after cerebral ischemia remain unclear. We examined long-term changes in the gut microbiota and systemic inflammatory cytokines after cerebral infarction in cynomolgus monkeys. Methods: Twelve monkeys underwent successful distal M1 segment of the left middle cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 46 publications
3
78
0
Order By: Relevance
“…The consequences of this remain unclear, as detrimental effects to regulatory T cells after AIS have been reported (51). Release into the systemic circulation of cytokines and chemokines produced in the brain after AIS may exert a potential influence on microbiota composition and dysbiosis (52). T lymphocytes, especially regulatory and γδT-cells, play a pivotal role in how the microbiota can modify infarct size and neurological function after AIS (7,53).…”
Section: The Brain-gut-microbiota Axis In Aismentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of this remain unclear, as detrimental effects to regulatory T cells after AIS have been reported (51). Release into the systemic circulation of cytokines and chemokines produced in the brain after AIS may exert a potential influence on microbiota composition and dysbiosis (52). T lymphocytes, especially regulatory and γδT-cells, play a pivotal role in how the microbiota can modify infarct size and neurological function after AIS (7,53).…”
Section: The Brain-gut-microbiota Axis In Aismentioning
confidence: 99%
“…An interesting experimental study showed that AIS in cynomolgus monkeys induced a long-term, persistent increase in levels of LPS and pro-inflammatory cytokines in plasma, which correlated with the relative abundance of the phylum Bacteroidetes in the gut microbiota. Additionally, intestinal dysbiosis and mucosal damage persisted for up to 12 months after AIS ( 52 ). Clinical evidences ( 56 , 57 ) concluded that after AIS the commensal flora changes in favor of opportunistic pathogens, such as Enterobacter, Megasphaera, Oscillibacter, Desulfovibrio, Odoribacter , and Akkermansia ( 58 ), instead of commensals such as Bacteroides, Prevotella , and Faecalibacterium .…”
Section: Pathophysiologymentioning
confidence: 99%
“…We observed that prolonged intestinal inflammatory pathology accompanies the changes that we see in bacterial abundance. More recently, mucosal and villi damage has been observed in the colons of cynomolgus monkeys at 1.5, 6, and 12 months after permanent MCAO [81]. Although specific mechanisms linking gut dysbiosis and stroke remain elusive, the most likely mechanisms include: increased permeability of the intestinal barrier and bacterial motility, suppression of systemic immunity, release of proinflammatory factors from the brain infarct, and activation of the sympathetic nervous system [82,83].…”
Section: Cells and Significant Increases In Cd4+ T Cells And Cd8+ T mentioning
confidence: 99%
“…Studies indicate the effect of intestinal microflora on a host stroke outcome, paying attention to two-way communication along the brain-gut axis [ 28 , 34 ]. Growth of Bacteroidetes after an ischemia was confirmed in monkeys [ 35 ]. Increased Bacteroidetes abundance was also found three days after the occurrence of an ischemic stroke in mice, which is considered a characteristic feature of post-stroke dysbiosis [ 28 ].…”
Section: Post-ischemic Brain Versus Gut Microbiotamentioning
confidence: 99%
“…In contrast, a clinical study in which stool samples were taken for two days after admission showed a decrease in Bacteroidetes levels in patients with an acute ischemic stroke and a transient ischemic attack [ 36 ]. In the study of monkeys after a focal brain ischemia, an increased relative abundance of Prevotella was found, suggesting that this type may be associated with an inflammatory response following a stroke [ 35 ]. In monkeys after a local cerebral ischemia, reduced relative levels of Faecalibacterium , Streptococcus , Lactobacillus and Oscillospira were observed [ 35 ].…”
Section: Post-ischemic Brain Versus Gut Microbiotamentioning
confidence: 99%